How your digital helper may undermine your welfare, and our democracy - Stucke, M; Ezrachi, A (University of California Press, 2018)
Digital assistants embody the dream of an effortless future, free from the shackles of yesteryear. A tool which caters for users’ our needs, excels at anticipating their our wants and delivers a personalized online environment. While digital assistants can certainly offer great value, a closer look reveals how in an algorithm and data driven world, one’s your digital assistant may ultimately serve the interests of others. It may be used to establish ed a controlled and manipulated personalized environment in which competition, welfare, privacy and democracy give way to corporate interests. The future is not necessarily bleak, but requires our attention if we want these assistants it to match the our euphoric effortless dream.